2001
DOI: 10.1177/039139880102401105
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of a Cell Module for Hybrid Liver Support

Abstract: Aim of the study was to evaluate a hybrid liver support system in a porcine model of acute liver failure, after hepatectomy. Pigs with a body weight of 70+/-18 kg underwent total hepatectomy and porto-cavo-caval shunting as well as ligation of the bile duct and the hepatic artery. Control animals were connected to the system (including capillary membrane plasma separation) containing a four compartment bioreactor with integral oxygenation and decentralized mass exchange but without liver cells. The treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Four discrete capillary membrane systems are woven to create a three-dimensional framework for decentralized cell perfusion with low metabolite gradients and decentralized oxygenation and CO 2 removal [141][142][143][144]. Such systems have primarily been characterized and proposed as a liver-support device [145][146][147][148][149][150]. Recent studies have also shown the suitability of the system as a tool to measure drug metabolism and enzyme induction in long term cultures of primary hepatocytes [140,151].…”
Section: Multicompartment Bioreactor Culturesmentioning
confidence: 99%
“…Four discrete capillary membrane systems are woven to create a three-dimensional framework for decentralized cell perfusion with low metabolite gradients and decentralized oxygenation and CO 2 removal [141][142][143][144]. Such systems have primarily been characterized and proposed as a liver-support device [145][146][147][148][149][150]. Recent studies have also shown the suitability of the system as a tool to measure drug metabolism and enzyme induction in long term cultures of primary hepatocytes [140,151].…”
Section: Multicompartment Bioreactor Culturesmentioning
confidence: 99%
“…Adequate oxygen supply inside BAL devices is crucial for maintenance of sufficient and stable liver-specific functions. Therefore, several BAL devices have been equipped with incorporated membrane or capillary oxygenators (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…8 We addressed technical issues by developing a hollow fiber-based four-compartment bioreactor technology, enabling decentralized oxygenation with low solute gradients and high-performance mass exchange. 9 Many cell types have been investigated to address the cell source issue. 10 Despite limited availability, primary human liver cells, isolated from explanted donor organs discarded from transplantation programs, would be a good cell source for addressing human liver metabolism.…”
mentioning
confidence: 99%